Pemberdayaan Siswa Smk Melalui Pemanfaatan Chatgpt Sebagai Penunjang Sumber Belajar Untuk Meningkatkan Literasi Digitalg - Mawarda Nurodanika; Ahmad Nur Azis; Julian Setiawan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aimed to improve the digital literacy of vocational high school (SMK) students through the use of chatGPT as a learning support tool. The program introduced the effective, ethical, and responsible use of artificial intelligence to enhance learning activities. The implementation included preparation, material presentation, demonstrations, hands-on practice, mentoring, and evaluation. Data were collected through questionnaires, observations, documentation and analyzed descriptively. The results indicate that students developed a better understanding of the use of ChatGPT and were able to utilize it effectively as a learning resource for seeking information and completing academic tasks. Furthermore, the program contributed to improvements in digital literacy and self-directed learning skills among participants. It also provided a more interactive learning experience, enhanced students' learning autonomy, and strengthened their readiness to use technology effectively, ethically, and responsibly in response to the demands of learning in the era of digital transformation.